Co/Mn-based 2D coordination polymers: synthesis, structure and ring opening polymerization - Gong, Yi; Prior, Timothy J.; Redshaw, Carl (Inorganica Chimica Acta, 2024)
The two-dimensional coordination polymers [Co(DMF)2L2]∙0.65H2O and [Mn(DMF)2L2]∙0.4H2O (L = N,N′-bis(glycinyl)pyromellitic diimide) have been prepared and structurally characterized by a variety of techniques including FTIR spectroscopy, powder and single crystal X-ray diffraction. Results for their use as catalysts in the ring opening polymerization of ε-caprolactone (ε-CL) and δ-valerolactone (δ-VL) are reported. High conversions were achievable at 130 °C, resulting in the formation of mostly cyclic polycaprolactone (PCL) and polyvalerolactone (PVL), respectively, with only a small number of linear polymers formed. Kinetic studies revealed the presence of two distinct rate steps, the second of which is assigned to the formation of an active decomposition product.
Keywords: 2D coordination polymers; Ring opening polymerization; ε-caprolactone; δ-valerolactone